Literatura e Ludicidade: o jogo intertextual como estratégia criativa - Venturim, Priscíla Andressa Crepaldi (2023)
The presented research focused on reflections and analysis involving the theme of literature and playfulness. From studies and our empirical knowledge on the subject, some guiding questions emerged in our investigation: playfulness as something intrinsic to human life that goes beyond the recent concept of the term "playful" and the game as a writing strategy. With the purpose of finding answers to these questions, we set, as a general objective, the analysis of three works: The Enigma of Infinity (2019) by Jacques Fux, Small Choreography of Goodbye (2021) by Aline Bei, and The Seven Rules of the Game (2014) by Miguel Jorge. To achieve the proposed objective, we based the research on the theoretical assumptions of Comparative Literature. This is, therefore, a qualitative research based on intertextual analysis, which aimed to analyze the interaction between literature and playfulness. Data collection was made possible through textual analysis and critical interpretation of the selected works. As a result of this investigative process, we understand that playfulness in literature transcends the boundaries of childhood and manifests itself as a creative and reflective tool in contemporary literary production. The research is grounded in the assumptions of Comparative Literature and utilizes a qualitative approach, focusing on intertextual analysis and the interaction between literature and playfulness. The main theorists cited in the dissertation include: Robert Escarpit (1970), Gilles Brougère (1998), Mariza Lajolo (1984), Roland Barthes (1987), Johan Huizinga (2012), and Roger Caillois (1990). These authors contribute to the understanding of playfulness as a creative and reflective tool in literary production, highlighting its social and historical relevance. The research emphasizes the importance of innovative writing that articulates playful elements in different literary genres, such as prose, poetic prose, and poetry.